Study of Religious Values in Sirah Nabawiyyah-Based Social Science Education - Abdul Mu'min Saud; Suwarma Al Muchtar; Didin Sarifudin (Budapest International Research and Critics University, 2022)
The purpose of this research is first, to find out how the concept of social studies education based on Sirah Nabawiyah is applied at SMPIT Asyifa Boarding School Jalancagak Subang, West Java. Second, to find out why the social studies learning system at SMPIT Asyifa is integrated with Islamic values. Third, to find out how the implementation of social studies learning at SMPIT Asyifa is integrated with Islamic values. Fourth, to find out how the advantages and disadvantages of social studies learning at SMPIT Asyifa Jalancagak Subang are integrated with Islamic values. This research uses a case study qualitative approach. Data was collected by means of interviews, observations, participation, focused discussions, observations and documentation studies. The research informants were the principal, homeroom teacher, in the field of curriculum, social studies teachers for grades VII, VIII, and IX, students in grades, VII, VIII, and IX at SMPIT Asyifa Boarding School Jalancagak Subang. The results of this study, found: (1) The integration of spiritual values in social studies learning is pursued through the example of the principal and teachers, the Head of Curriculum as a translator of the school's vision and mission, the mission of the pesantren, and the head of the dormitory, as well as the implementation of learning programs that nuanced Islamic spiritual values. (2) While the implementation of social science learning (IPS) integrated with Islamic spiritual values is carried out with strategies, namely: always mentioning the names of Allah (asmaul Husna), use of terms, visual illustrations in the form of pictures or slides, applications or examples. , inserting relevant verses of the Qur'an or hadith, tracing the history of the Prophet.